Outcome of conventional and alternative assessment during online teaching and learning mode between open book and recall test - Ismail, Soraya; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Abdul Rahim, Roslina; Khaing, Aye Thi; Mohd Radzuan, Hazulin; Ismawi, Hidayatul Radziah; Mat Harun, Noraihan; Mohamed Bakrim, Norbaiyah; Abd. Rahim, Nour El Huda; Mohd Noor, Mohd Fadly; Wan Omar, Wan Fatein Nabeila; et al. (2021)
This was a poster submitted to the International Putra Innovative Teaching and Learning (PicTL) 2020 poster competition from 22-30 October 2020, organized by University Putra Malaysia. It reported on the outcome of conventional and alternative assessment during online teaching and learning mode between an open book and recall best for IIUM Year 1 medical students for the academic year 2019-2020. This poster won a Bronze Medal Award.